108 Management of vein of galen on cardiopulmonary bypass. (22nd November 2019) - Robertson, Alex; Issitt, Richard
Abstract : Surgical repair of cardiac defects using cardiopulmonary bypass (CPB) in patients with vein of Galen malformation (VGM), presents a serious challenge to the extent that it has been reported only once before. Multiple case reports describe poor outcome, or the use of hybrid procedures avoiding CPB and recommend conservative management until the VGM has been eradicated. Of particular concern is the high blood flow shunting through the VGM which may be so significant that it might reduce cerebral and somatic perfusion to the extent that hypoxic ischaemic injury is induced. Using a combination of high cardiac index and pH-stat blood gas management maximises cerebral protection whilst cooling the patient to 18°C allows Deep Hypothermic Circulatory Arrest (DHCA) facilitated repair of the cardiac lesion to be undertaken safely. By applying resistance to the venous drainage, a positive central venous pressure (CVP) can be maintained avoiding decompression of the central veins which would otherwise exacerbate the cerebral shunt flow. Using a case study of a 23 day old female neonate with dissection of the patent ductus arteriosus (PDA) and pulmonary artery in combination with VGM, we present the key criteria for successful management and the physiological mechanisms.